Solar hydrogen production via thermochemical magnesium oxide – Magnesium sulfate water splitting cycle - Rahul R. Bhosale (6467102) (2020)
This investigation reports the thermodynamic scrutiny of the MgO/MgSO4 water-splitting cycle. At the initial stage, the thermal reduction temperature required for the commencement of the thermal dissociation of MgSO4 (in the absence of inert Ar) and the maximum temperature below which the water-splitting reaction is feasible is identified by performing thermodynamic equilibrium calculations. The influence of inert Ar as the carrier gas on the thermal reduction temperature is also explored. After identifying the required operating temperatures, the second law efficiency analysis predicts the process parameters of this cycle. Overall analysis confirms that although the rise in the molar flow rate of Ar from 1 to 50 mol/s results in a decrease in the thermal reduction temperature from 1490 K to 1282 K, the solar-to-fuel energy conversion efficiency is adversely affected and reduces from 47.7% to 18.1%. As per the analysis, this cycle achieved the highest solar-to-fuel energy conversion efficiency (47.7%) at the molar flow rate of Ar = 1 mol/s, thermal reduction temperature = 1490 K, and water splitting temperature = 475 K. Further increment in the solar-to-fuel energy conversion efficiency up to 62.5% is possible if 50% of the heat recuperation is applied. Other Information Published in: Fuel License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.fuel.2020.117892